Wearable Hybrid Device Capable of Interactive Perception with Pressure Sensing and Visualization (Adv. Funct. Mater. 44/2022). (28th October 2022) - Guo, Yunjian; Li, Hao; Li, Yang; Wei, Xiao; Gao, Song; Yue, Wenjing; Zhang, Chunwei; Yin, Feifei; Zhao, Songfang; Kim, Nam‐Young; Shen, Guozhen
Abstract : Wearable Interactive Devices In article number 2203585, Yang Li, Guozhen Shen, and co‐workers propose an integrated hybrid device based on ionic sensing and electrochromic display, which is inspired by the two‐in‐one response of an octopus. Benefiting from the excellent comprehensive performance of the device, several novel applications involving interactive pressure perception are explored and verified. Notably, multiple customized systems with improved design flexibility are implemented to provide remote monitoring and visual warning of behavioral states and physiological parameters.